Pengaruh Ekstrak Wortel (Daucus Carota Linn.) Terhadap Aterosklerosis Pada Burung Puyuh Jantan (Cortunic-Cortunix Japonica) - Suhatri Suhatri; Hel Amir; Zet Rizal (STIFARM Padang, 2014)
Has done research the effect of extracts of carrot (Daucus carota Linn.) Against atherosclerosis in male quail (Cortunix-cortunix japonica). Atherosclerosis induced by administering Prophylthiouracyl (PTU) and high-fat foods (MLT). Carrot extract dose given on quail is 50 mg / kg BW, 100 mg / kg BW and 200 mg / Kg BW on quail males given orally for 60 Days. The results showed that the administration of carrot extract at a dose of 100 mg / kg BW and 200 mg / kg BW can prevent the formation of atherosclerosis in male quail, marked on the wall thickness of the aorta, the aortic lumen and extensive damage to endothelial cells was not different from the negative control (P < 0.05). Carrot extract dose of 50 mg / kg BW for 60 days can not be pried prevent its established atherosclerosis, characterized in aortic wall thickness, area of the aortic lumen and endothelial cell damage is not different from the positive control (P> 0.05).